Evaluation of Selected Species of Fodder Trees Cultivated for Feeding Ruminant Animals in the Hills of Nepal - Khanal, Ramesh C.; Upreti, Chet R. (Nepal Agriculture Research Journal, 2014)
Leaves and twigs from four species of tree fodders, Aetocarpus lakoocha (AL), bauhinia purpurea (BP), Garuga pinnata (GP) and Ficus sroxburghii (FR), cultivated widely for feeding ruminants in the hills of Nepal and maintained at the Agriculture Research Station (Goat), Bandipur were investigated for there chemical composition, and nutrient intake, digestibility, and growth rate in growing female goats. Differences occurred between species of tree fodders on nutrient composition, which contained 286, 342, 312, and 263 g/kg DM; 174, 98, 116 and 178 g/kg total ash; 137, 163, 140, and 119 g/kg CP; 440, 458, 437, and 451 g/kg NDF; 383, 407, 382, and 406 g/kg ADF; 177, 135, 181, and 143 g/kg ADL; 19.5, 21.6, 20.9, and 29.3 g/kg Ca; and 2.2, 2.8, 2.4, and 2.5 g/kg P on DM basis for AL, BP, GP, and FR, respectively. The DM intake was higher for goats fed AL (432 g/d) and GP (428 g/d) than BP (342 g/d) or FR (306 g/d). Nutrient digestibility was higher for goats fed AL and GP, except Ca, which was higher for goats fed FR. Similarly, highest daily weight gain was observed for goats fed AL (71 g/d) and GP (64 g/d) than either of BP (54 g/d) or FR (30 g/d). Overall, leaves and twigs from these tree fodders supported moderate growth, but may not be advisable for maximum production. Nepal Agric. Res. J. Vol. 8, 2007, pp. 88-94 DOI: http://dx.doi.org/10.3126/narj.v8i0.11600